MOTIF DAN MAKNA BISNIS SYARIAH BAGI PENGUSAHA MUSLIM INDONESIA DI PEKANBARU - Gita Adias Putri; Welly Wirman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This study aims to examine the extent to which the development of sharia business over the past 10 years, besides that there are many factors that the majority of Muslims carry the theme of Islamic sharia in business activities, for example such as trading services in accordance with Islamic sharia. This triggers the existence of associations or communities that carry the theme of Islamic sharia in its business activities. One of them is Kpmi Indonesian Muslim Entrepreneurs Community. which must be known about their motives and meanings in conducting Islamic business, after leaving the conventional business.          This study uses qualitative research methods with a phenomenological approach. The research subjects consisted of six people consisting of chairpersons, secretaries, treasurers, and members of the Muslim Entrepreneurs Community in the city of Pekanbaru (KPMI) selected using snowball sampling techniques. Data collection was carried out through in-depth interviews, observation and documentation. To validate the data, the writer uses the technique of extending participation, perseverance of observation and triangulation.           The results showed that the motives of KPMI members in conducting sharia business in their business activities consisted of motives which included drawing closer to Allah, the motives to stay away from usury, muamalah motives, Al-Qur'an love motives, family support motives. Various motives because it is the background of Indonesian Muslim entrepreneurs in the city of Pekanbaru in implementing business based on Islamic sharia. The purpose or expectation motive (in order to motive) which is the objective of informants' participation in implementing syraiah business, which consists of expectations for the motive for ukhuwah Islamiyah. Get guidance, open up jobs, share knowledge with fellow Muslim entrepreneurs. Whereas the meaning of sharia business is explained to Indonesian Muslim entrepreneurs in the city of Pekanbaru, which includes profit-material and non-material benefits, Sustainability. Meaningful blessings, favors and gratitude that we get from our hard work, this we can get by running a halal business, with that Allah gives blessings to the people he wants.               Keywords: Community, motives, Meaning. Sharia Business